Advanced Welding Technology in Metals - Oliveira, João Pedro; Zeng, Zhi (MDPI - Multidisciplinary Digital Publishing Institute, 2022)
Welding is widely used by both academia and industry to create similar and dissimilar joints aiming to create a complex shape structure and to couple the mechanical properties of different materials into a single monolithic structure. In this book, a collection of peer-reviewed works on the welding of advanced engineering alloys is presented. Both solid-state and fusion-based welding technologies are presented. These works employed advanced microstructure characterization to evaluate how the selection of process parameters impacts the microstructure and mechanical properties of the welded joints. Moreover, three comprehensive review works are also included, providing an in-depth overview of distinct topics. We hope that this collection of works is of interest to the community so that welding technologies continue to grow further in the future.